Developing English Vocabulary Materials Based on Moluccas Content for Elementary School Students - Souhoka, Ingrid Bella (Huele: Journal of Applied Linguistics, Literature and Culture, 2022)
This study aimed to develop English vocabul ary materials based on Moluccas content for elementary school students. The research used a Research and Development (R&D) design, adapting the Borg and Gall model. The study was conducted in five main steps: research and information collecting, planning, developing a preliminary form of the product, preliminary field testing, and main product revision. The preliminary field testing involved expert validation, which resulted in a score of 76.6%, indicating the materials were appropriate for use. The developed materials covered vocabulary related to Moluccan themes such as traditional fruits (rujak), local animals, the World Peace Gong site, traditional Moluccan clothing, and Moluccan heroes. The study concluded that the English vocabulary materials based on Moluccas content were successfully developed and can be an effective teaching resource for elementary students in the region.